STUDY OF THE TISSUE REACTION OF THE VAGINAL WALL TO IMPLANTED POLYPROPYLENE PROSTHESES - Игорь Александрович Эйзенах; Максим Александрович Бакарев; Галина Анатольевна Лапий; Олег Иванович Бондарев; Вадим Гельевич Мозес; Кира Борисовна Мозес (Медицина в Кузбассе)
The aim of the research – to study the frequency of erosion of the vaginal mucosa and tissue response to polypropylene prostheses by morphometry in patients operated on for anterior genital prolapse.